Book Review:A. RIGO – M. TRIZIO – E. DESPOTAKIS (eds.), Byzantine Hagiography: Texts, Themes and Projects (Studies in Byzantine History and Civilization, 13), Turnhout 2018 - ΚΩΝΣΤΑΝΤΙΝΟΥ Σταυρούλα Ανδρέα (Byzantina Symmeikta, 2020)
Book Review: ANTONIO RIGO – MICHELE TRIZIO – ELEFTHERIOS DESPOTAKIS (eds.), Byzantine Hagiography: Texts, Themes and Projects (Studies in Byzantine History and Civilization, 13), Turnhout 2018